Harvest Gypsies in the San Francisco News, Oct. 10, 1936 - San Francisco News:::Publisher:::::::::::: (San Francisco News, 2024)
Page 14 of the San Francisco News, Oct. 10, 1936, with the Sixth Harvest Gypsies article including photographs by Dorothea Lange.